Holocene paleohydrology from Lake of the Woods and Shoal Lake cores using ostracodes, thecamoebians and sediment properties - Mellors, Trevor (2010)
Ten sediment cores (2.0-8.5 m long) from various locations in Lake of the Woods (LOTWs) and Shoal Lake (SL) were recovered in August 2006, using a Kullenberg piston corer. From the study of the macrofossils (primarily ostracodes and thecamoebians) and the sediments in six processed cores, variations in paleoconditions were observed both spatially and temporally, and the timing of these changes were identified in over 10,000 years of postglacial history. Ostracodes disappeared from the LOTWs record from about 9000 to 7600 calendar years before present (BP) (about 5800 in SL), after LOTWs became isolated from glacial Lake Agassiz. Thecamoebians appeared in many cores around 2000 calendar years BP, with the earliest appearance at 9200. Buried paleosols in three cores indicate portions of the lake dried on several occasions during the Hypsithermal, perhaps indicating the region’s future climate response. One core contained a pink clay bed indicative of the Marquette readvance about 11,300 years (BP), and the subsequent input of water from the Superior basin. October 2010